Validity and Reliability of the Amharic Version of the World Health Organization’s Quality of Life Questionnaire (WHOQOL-BREF) in Patients with Diagnosed Type 2 Diabetes in Felege Hiwot Referral Hospital, Ethiopia - Kidist Reba; Bizuayehu Walle Birhane; Hordofa Gutema (Journal of Diabetes Research)
Background. Although it is largely preventable, type 2 diabetes is the most common type and accounts for the vast majority of diabetes cases worldwide. Objective. To assess the validity and reliability of the Amharic version of the abbreviated World Health Organization Quality of Life (WHOQOL-BREF) instrument for measuring quality of life in people with diagnosed type 2 diabetes. Methods. The Amharic version of the abbreviated World Health Organization Quality of Life instrument was administered to 344 patients with diagnosed type 2 diabetes in Felege Hiwot Referral Hospital. Contribution of domain scores to QOL facets was assessed using multiple linear regression. Reliability assessment was done by using Cronbach’s alpha coefficient. Construct validity was examined using exploratory and confirmatory factor analyses. Result. The Amharic version of the abbreviated World Health Organization Quality of Life instrument has acceptable internal consistency. Confirmatory factor analysis has shown acceptable goodness of fit for 4 domain models. The physical, psychological, and environmental domains have a statistically significant contribution in explaining overall quality of life, while only physical and psychological domains have significant contribution in explaining the general health facet. Conclusion. The Amharic version of the abbreviated World Health Organization Quality of Life instrument is appropriate for patients with diagnosed type 2 diabetes. The overall finding of analysis implies that the Amharic version of the abbreviated World Health Organization Quality of Life instrument has internal consistency and validity to investigate quality of life among patients with diagnosed type 2 diabetes, and it can be used for studies which are going to be conducted in Ethiopia.